A review of echocardiograms in hypertensive patients greater than 60 years in a community based family medicine program - Shideh Doroudi; Michael D. DeLisi; Vincent A. DeBari (Greater Baltimore Medical Center, 2017)
Background: Heart disease as a result of Hypertension is known to occur. Anatomical and functional changes of the heart can easily be detected by echocardiography, which is a safe and readily available study. Objectives: The aims of this study were to evaluate the prevalence of common echocardiographic changes in chronic hypertensive patients and to compare these changes in male and female populations. Design/methods: The study was a community-based cross-sectional study, on 227 hypertensive patients, 60 years and older, seen in St. Joseph's Family Medicine at Clifton, with integrated clinical and echocardiographic data. Results: Study population consisted of 227 hypertensive patients, over the age of 60 years who had echocardiography done. Overall 92.5% of the echocardiograms had abnormal findings including but not limited to TR, Diastolic dysfunction, MR, and LVH. There was significant difference between the rate of MR in male and female population. Conclusion: A variety of echocardiographic abnormalities can be found in hypertensive patients. Drug selection in hypertension should be driven by the underlying cardiac pathology. Certain drugs have more effectiveness for diastolic dysfunction, LVH, systolic dysfunction and pulmonary hypertension and are superior choices when these conditions are present. Echocardiogram is a non-invasive and easily available tool in order to help us to select the best treatment strategy to optimize hypertensive control in the challenging group of elderly patients. The results of our study should influence us to liberally use echocardiography in these patients to guide treatment decision and drug selection. Abbreviations: LVH: left ventricular hypertrophy; MR: mitral valve regurgitation; TR: tricuspidvalve regurgitation; LVD: left ventricular dilation; LVEF: left ventricular ejection fraction